Genetic Diversity of Aphid Species Attacking Amaranth and Nightshades in Different Agro-Ecological Zones of Kenya and Tanzania - Kipnyargis, Alex C. (University of Embu, 2016)
Aphids are the major pests of vegetables leading to a significant yield loss in African indigenous vegetables including amaranth and nightshades. Information on the types of aphids that infest these vegetables and their genetic diversity in Kenya and Tanzania is scanty. This is an important diagnostic component in developing management strategies such as integrated pest management and early detection and control of invasive species. This study used a fragment of the mitochondrial cytochrome c oxidase subunit I (COI) gene region called the barcode region to characterize the species of aphids that attack amaranth and nightshades in different agro-ecological regions of Kenya and Tanzania. Individual aphid samples were collected in 22 localities of amaranth and nightshade growing zones of the two countries, representing low, mid and high altitude agro-ecological zones. Total DNA was isolated and amplified using universal barcoding primers targeting the 5’ end of the COI barcode region. There was a strong homology (≥ 98% identity) in nucleotide sequences of the barcode region using the Basic Local Alignment Search tool for nucleotides (BLASTn) in the GenBank to four main species of aphids namely: Myzus persicae, Aphis fabae, Aphis craccivora and Macrosiphum euphorbiae. Further, three subspecies of the black bean aphid were identified as A. fabae fabae, A. fabae ciirciacanthoidis and A. fabae solanella. Intra-specific nucleotide diversity indicated that M. euphorbiae had no genetic diversity (0.0%); while A. fabae had the highest diversity (0.8%). The lowest inter-specific diversity was observed between A. fabae and A. craccivora (6.3%) while the highest was observed between A. craccivora and M. persicase (10.6%). The phylogenetic tree constructed using the maximum likelihood model showed each individual species clustering in robust clades irrespective of the host crop or the locality from which it was collected. This confirmed the BLASTn results. The principal coordinate analysis (PCoA) and the haplotype network analyses further confirmed these results by showing species clustering together in their space and haplotypes, respectively. Overall, COI successfully identified the species of aphid infesting amaranth and nightshades. This forms an important diagnostic tool for management strategies, early detection of newly evolving biotypes, deployment of resistant crop cultivars and containment of invasive species.